(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Morinda lucida Benth (Rubiaceae) commonly known as brimstone has been used in ethnomedicine for wound healing. However, the presentation of this plant in a conventional dosage form for standard dosing and patient acceptance has not been done. Objectives: This study was designed to formulate the extracts into pharmaceutical cream and investigate its wound healing activity in animal model. Methods: Leaf ethanol (LE), Leaf aqueous (LAQ), stem-bark ethanol (SE) and stem-bark aqueous (SAQ) extracts of M. Lucida were prepared by maceration. Pharmaceutical creams were prepared by standard procedures using 10%w/w extract and assessed by pH, viscosity, extrudability and spreadability. Extracts and creams were evaluated in Wistar rats using incision and excision wound models. For incision, animals were euthanized after 14 days and wound site tissues collected for histology. Excision model was based on wound contraction, closure and epithelialization for 20 days. Results: The creams had acceptable pH, viscosity, extrudability and spreading times. Histology photomicrographs showed that LE, LAQ and 10% LE cream showed dense, well-arranged and well-positioned collagen, with moderate diffuse cellular dermis infiltration compared to controls. All extracts and cream formulations enhanced wound healing compared to their negative controls while leaf ethanol cream showed optimal activity in significantly (<0.05) reducing wound diameter compared to gentamycin as positive control. Conclusion: Morinda lucida extracts and cream formulations demonstrated significant (<0.05) wound-healing activity in-vivo, in comparison with negative controls and can be improved for translational outcomes.